Toughness enhancement of polyamide 1012 with intermolecular hydrogen bonding with 3-pentadecylphenol - Jing Lu; Qin Ma; Jianqi Yao; Jiajie Yin; Ruiyan Zhang; Faliang Luo (eXPRESS Polymer Letters)
In order to improve the impact toughness of polyamide 1012 (PA1012) by reducing the amount of hydrogen bonding resulting from PA1012 itself, 3-pentadecylphenol (PDP) was considered to be added into PA1012 using melting extrusion. The hydrogen bonding interaction between PA1012 and PDP was characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance (NMR). The effects of PDP on the crystallization, melting process, and mechanical behavior of PA1012 were tested in detail. The results show that the PDP can reduce the temperature of PA1012 crystallization and melting but it can significantly improve elongation at break and impact toughness. The notched impact strength of the PA1012/PDP composites containing 20 wt% PDP reached to 70.6 kJ·m–2, which is about seven times that of the neat PA1012. The effects of PDP on PA1012 properties is ascribed to hydrogen bonding interaction between hydrogen bonding between phenol hydroxyl groups and amino groups on PA1012 chains. The deduction was also verified by adding acetylated 3-pentadecylphenol (APDP) to modify PA1012. It is believed the research will open up new prospects for the wide application of PA1012 toughening.